Risk, Liquidity, and Performance: Evidence from the Commercial Banks in Bangladesh - Bhowmik, Probir Kumar; Islam, Ariful (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Research Originality: This study examines the interplay between bank risk, liquidity, and profitability in Bangladesh's banking sector. Using a fresh approach, it shows their combined impact on stability and growth in emerging markets. It provides practical insights for banks to effectively manage these factors and achieve long-term resilience. Research Objectives: The study aims to investigate the interconnected influence of non-performing loan ratios and liquidity levels on profitability, and to analyze the effects of total asset growth, loan growth, and cost-to-income ratios on these dynamics. Research Methods: The study used a panel dataset of 31 listed commercial banks from 2012 to 2022. Ordinary Least Squares (OLS) regression was primarily employed, followed by Prais–Winsten regression with corrected standard errors (PCSEs) for correlated panels to validate the findings. Empirical Result: The research indicates that liquidity (LIQ) has a positive impact on profitability, with the net interest margin (NIM) being significantly influenced by non-performing loans. The control variable, SIZE, also showed statistical significance in performance. Implications: This study highlights the significance of asset quality, liquidity management, loan composition, and operational efficiency in determining bank profitability, providing valuable insights for bank managers and policymakers in emerging economies seeking to enhance their financial performance. JEL Classification: C33, G21, G32, C58